The Human Face of Housing Policy for Rural Elders in Maine - Butler, Sandra (Maine Policy Review, 2003)
Sandra Butler reflects on the ways in which the older households she has been encountering in her recent in-depth research in Washington County match those described by Stephen Golant in his article in this issue on the needs of elderly homeowners and the solutions to those needs. Butler’s research is based on extensive interviews with volunteers and clients of the Senior Companion Program, which has as one of its primary purposes helping elders remain in their homes as long as possible. Butler notes that she was surprised to learn how many subsidized housing complexes exist in Washington County. A number of the elders interviewed live in such housing, while others remain (sometimes precariously) in their own homes. The quotations and vignettes Butler provides here give readers “the human face” of housing policy for some of Maine’s rural elders.